The overexpression of KIFC1 was associated with the proliferation and prognosis of non-small cell lung cancer - Liu, Yafang; Zhan, Ping; Zhou, Zejun; Xing, Ze; Zhu, Suhua; Ma, Chenhui; Li, Qian; Zhu, Qingqing; Miao, Yingying; Zhang, Jianya; Lv, Tangfeng; Song, Yong (Journal of Thoracic Disease, 2016)
Background: The kinesin family member C1 (KIFC1, also known as HSET) is a kinesin superfamily protein (KIFs). Although KIFC1 acts as a crucial role in the development of several human cancers, the KIFC1 expression profile and functional remain unclear in non-small cell lung cancer (NSCLC). Methods: We collected the fresh NSCLC samples and paired normal lung tissue in patients with lung cancer operation, and detected KIFC1 expression using quantitative reverse-transcription polymerase chain reaction (qRT-PCR) and Western bloting. To expand on previous smaller-scale studies, NSCLC tissue microarrays (TMA) were analyzed by IHC. Finally, cell lines were employed to further probe the potential mechanisms, Results: In this study, we described that KIFC1 was significantly upregulated in NSCLC tissues compared with the corresponding normal tissues. Moreover, KIFC1 overexpression was associated with the poor overall survival (OS) of NSCLC patients, and siRNA-mediated knockdown of KIFC1 significantly suppressed tumor cell proliferation in vitro. Further verification showed that inhibition of KIFC1 gene expression caused the upregulation of the cyclin-dependent kinases inhibitor p21 and downregulation of the cell cycle driver protein cdc2, which arrested cells in the G2-M phase. Conclusions: we report that increased KIFC1 expression may promote cell proliferation and identified it as a biomarker of unfavorable prognosis in NSCLC patients.